2022
DOI: 10.1002/ijgo.14334
|View full text |Cite
|
Sign up to set email alerts
|

Low‐dose aspirin use in the first trimester of pregnancy and odds of congenital anomalies: A meta‐analysis of randomized controlled trials

Abstract: Background Daily low‐dose aspirin (LDA) is recommended in high‐risk pregnancies. However, its safety profile in the first trimester has not been well documented. Objectives To determine if LDA exposure during the first trimester of pregnancy is associated with higher odds of congenital structural anomalies. Search Strategy PubMed, Embase, Web of Science, Cochrane Central Register of Controlled Trials, and http://clinicaltrials.gov were systematically searched. Selection Criteria Randomized controlled trials (R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…Although prophylactic aspirin in low doses is considered safe for use in pregnancy, its use might increase the risk of bleeding, e.g., epistaxis, small skin bleedings, gastrointestinal discomfort, or postpartum hemorrhage ( 6 , 98 , 106 , 107 ). A few older studies have raised concern for congenital anomalies including gastroschisis and cryptorchidism after fetal exposure to aspirin in analgetic doses in early pregnancy ( 108 110 ), but this has not been found in a recent meta-analysis ( 111 ). Prophylactic low-dose aspirin is mainly initiated after the organogenesis and is discontinued around 36–37 gestational weeks, i.e., well before labor normally starts.…”
Section: Prophylactic Aspirin For Prevention Of Preeclampsiamentioning
confidence: 99%
“…Although prophylactic aspirin in low doses is considered safe for use in pregnancy, its use might increase the risk of bleeding, e.g., epistaxis, small skin bleedings, gastrointestinal discomfort, or postpartum hemorrhage ( 6 , 98 , 106 , 107 ). A few older studies have raised concern for congenital anomalies including gastroschisis and cryptorchidism after fetal exposure to aspirin in analgetic doses in early pregnancy ( 108 110 ), but this has not been found in a recent meta-analysis ( 111 ). Prophylactic low-dose aspirin is mainly initiated after the organogenesis and is discontinued around 36–37 gestational weeks, i.e., well before labor normally starts.…”
Section: Prophylactic Aspirin For Prevention Of Preeclampsiamentioning
confidence: 99%
“…Therefore, it should be explained in detail to every patient why higher doses must be used in her treatment whenever that is necessary. To date, no association of LDA with the development of birth defects, malformations, miscarriages, and premature closure of the ductus arteriosus has been detected [ 58 , 59 , 60 , 61 ]. One study evaluating the use of paracetamol, ibuprofen, and aspirin on 185,617 pregnant patients showed the possibility of increased risk of cerebral palsy in women exposed to aspirin during pregnancy.…”
Section: Is Aspirin Right For Every Woman?mentioning
confidence: 99%
“…One RCT study enrolling 1,288 women, among whom 615 started using LDA before pregnancy and kept taking the medication throughout the whole pregnancy, suggested that exposure to LDA during pregnancy did not increase the risk of congenital malformations [12]. A recent meta-analysis included 8 RCTs (7564 participants assigned to LDA less than 14 weeks of gestation and 7670 serving as controls) and the results suggested no evidence of safety concerns regarding LDA teratogenicity [13]. However, LDA exposure of less than 14 weeks was selected as the criterion to delineate the first trimester rather than the embryonic period which demonstrates the critical window of teratogenicity.…”
Section: Introductionmentioning
confidence: 99%